Automating Attack and Defense Strategies in Cybersecurity - Ionut LATES; Catalin BOJA (Informatică economică, 2025)
Given the ongoing development and variety of cyber threats, there is a growing urgency for a proactive and efficient approach to IT security. This article presents a novel approach to automating cyber security attack and defense techniques by using automated Cyber Range scenario development. In light of the intricate and ever-changing nature of the current cyber context, characterized by the continuous discovery of new vulnerabilities and quick evolution of attacks, it is imperative to establish effective and flexible testing and training methodologies. Therefore, by utilizing specific data such as operating system versions, application versions, and recog-nized vulnerabilities (CVEs), it becomes feasible to automatically generate appropriate and authentic test scenarios inside a Cyber Range. There are several advantages to using this strategy. Organizations can enhance the efficiency and accuracy of their cybersecurity assessment process by using a Cyber Range scenario automation platform. Additionally, automation facilitates swift adjustment to emerging threats and technological advancements, allowing for the prompt detection and resolution of weaknesses in a more expedient and effective manner. Nevertheless, the process of adopting such a solution is not devoid of its difficulties. These encompass technical factors like the platform's ability to work well with other systems and its capacity to handle growth, as well as conceptual factors like guaranteeing that automatically created scenarios are both meaningful and realistic. Nevertheless, it is crucial to recognize and tackle these obstacles in order to effectively exploit the capabilities of automation in the Cyber Range. To summarize, the implementation of automated Cyber Range scenario production is not just a development, but a crucial requirement for effectively handling the intricacy and volatility of contemporary cyber threats. Organizations can enhance their ability to defend against cyber threats and improve their response to the dynamic digital landscape by implementing creative strategies.